THE ROLE OF SOCIAL MEDIA IN INFLUENCING ADOLESCENT HEALTH BEHAVIOR: A REVIEW FROM PUBLIC HEALTH, PSYCHOLOGY, AND DIGITAL COMMUNICATION PERSPECTIVES - Riady, Yasir; Samsidar, Samsidar; Kandi, Kandi (MSJ : Majority Science Journal, 2025)
This study aims to analyze the role of social media in influencing adolescent health behaviors from the perspectives of public health, psychology, and digital communication. The method used was qualitative research with a descriptive approach, through in-depth interviews, focus group discussions (FGDs), observation, and analysis of social media content frequently accessed by adolescents. The results show that social media is a primary source of health information for adolescents and has a dual influence. On the positive side, social media encourages healthy lifestyles, increases motivation, and provides easy access to health education. However, on the negative side, it can spread misinformation, encourage extreme diets, and psychological stress due to social comparison and the fear of missing out. The multidisciplinary analysis confirms that public health views social media as an effective campaign tool, psychology highlights social and emotional influences, while digital communication highlights the importance of creative content and the risks of algorithms. This study emphasizes the need for strong digital and health literacy, as well as collaboration between health workers and influencers to optimally utilize social media as a means of adolescent health education.